Pengaruh Faktor Sosial Ekonomi Terhadap Partisipasi Dalam Program Keluarga Berencana di Kota Bekasi Provinsi Jawa Barat - Reihana Anisa, (2022)
Bekasi City is a city that has population problems with a high birth rate and is also a city that participates in the Family Planning program to reduce the birth rate. This research was conducted with the aim of knowing the effect of income level, education level ,and employment have influence on participation in the Family Planning program in Bekasi City and looking at the problems and key variables that can support the family planning program so that it is implemented properly and reduces the birth rate. The analytical technique used in this research is a sustainability analysis technique using Micmac software. The results of this research are 1) the level of income and occupation have an influence on participation in the family planning program, while the level of education has no effect on participation in the family planning program, 2) this study classifies several variables that have been broken down from three clusters of variables into four topologies. i.e. a) determinant variable i.e.Information on family planning programs, active status of family planning participants, indicators of career success, reasons for work, and amount of income, b) relay variables, namely the existence of facilities, government support and concerns about increasing needs, c) output variables, namely the need for living expenses, basic desire, recent education and partner support, and the autonomous variable, namely the high level of education, will affect a person's insight into the family planning program.